Fostering Students' Motivation on Speaking through Talking Stick and Snowball Throwing Method - Susilowati Susilowati; Siti Aimah; Testiana Deni Wijayatiningsih (Universitas Muhammadiyah Semarang, 2017)
This research was a study to examine the students motivation on speakingthrough talking stick and snowball throwing. It used descriptive quantitative. It meant that this research would find the students motivation toward the use of talking stick and snowball throwing method. The subect of research was the eighth grade of SMPN 3 Tegowanu. There were 44 students. The data analysis of this research were questionnaire and video documentation. Based on the research result, the students motivation of questionnaire were3.38 students response very good in the use of talking stick in the experimental class. Than, there were 3.00 students response was good in the use of snowball throwing method. It meant that the students have a motivation to the learning process especially in speaking skill. Meanwhile, the result of the video documentation showed that the students motivation became better than in the previous meeting. The students who really felt ashamed at the beginning now they are not as ashamed as before. The students be more confident that at the beginning they always hide their face and ashamed to speak up because of less confident. Even their motivation for sepaking much better after being given the method of talking stick and snowball throwing. Then, the researcher suggests that the teacher could use talking stick and snowball throwing method in teaching speaking to achiev students speaking ability.